ANALYSIS OF SERANG REGENCY INFRASTUCTURE SERVICE SATISFACTION INDEX - Agus Lukman Hakim; Pandri Ferdias; Agus Sjafari; Muhammad Haekal Saniarjuna; Hanifah Hanifah; Siti Yuniar (Jurnal Administrasi Publik, 2025)
This research aims to determine the level of public satisfaction with the implementation of public services in the infrastructure sector provided by the Regional Government of Serang Regency, as well as the efforts of the local government to improve infrastructure services in Serang Regency. This study was conducted on the local government of Serang Regency. The research period lasted for two months, from July to September 2024. The variables to be examined are related to Physical Availability, Physical Quality, Appropriateness, Utility, and Contribution. The data used is primary data in the form of questionnaires distributed to the residents of Serang Regency aged over 17 years, spread across 29 districts, with a sample size of 205. The sampling technique used is multistage random sampling. The analysis technique employed is quantitative descriptive with the Infrastructure Service Satisfaction Index (IKLI) model. The results of the study indicate that the Infrastructure Service Satisfaction Index value for Serang Regency in 2024 is 2.62, equivalent to 65.62, which falls under the criteria of being fairly satisfied. This result shows that the residents of Serang Regency feel that the performance of the Serang Regency local government in priority infrastructure services is quite good and satisfactory. However, there is still a need for improvements in priority infrastructure services, particularly in bridge services, clean water, housing/settlements, and land transportation.